IMPACT OF “NIMBY" CONFLICT MANAGEMENT ON ENTERPRISE GROWTH. A CASE OF BUI DAM PROJECT IN GHANA. - Ayamba, Emmanuel Caesar (Archives of Business Research, 2018)
Not in my backyard is an important aspect affecting the establishment of large projects in the society that are deemed to have negative effect. The purpose of this paper was to study how the phenomenon of not in my backyard could impact on conflict management and enterprise growth resulting from the construction of the Bui dam project in Ghana. The study employed both primary and secondary data in the analysis process while making use of linear regression models to explain linear relationship between the variables. The empirical results indicated that a substantive relationship exists between the factors affecting the NIMBY attitude in the current society. Implying if adequate information is made available to the publics the expected reactions would be positive whereas the reverse is true